2022
DOI: 10.1039/d2cp01763f
|View full text |Cite
|
Sign up to set email alerts
|

The magnetic properties of pressurized CsV3Sb5 calculated by using a hybrid functional

Abstract: Based on the hybrid functional, we find that the magnetic moment on vanadium atoms in pressurized CsV3Sb5 can be triggered by the phase transition from ISD to pristine pattern combined with the suppression of CDWs by pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Conversely, using a hybrid functional, the calculated structural parameters and band gap are more consistent with experimental data . Our previous research has also demonstrated the ability of the hybrid functional to accurately describe the pressure-induced spin crossover behaviors of strongly correlated materials such as Fe-bearing MgO, MnPS 3 , and CsV 3 Sb 5 . It should be noted that for the study of Lu–N–H materials the hybrid functional method outperforms the GGA + U method.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…Conversely, using a hybrid functional, the calculated structural parameters and band gap are more consistent with experimental data . Our previous research has also demonstrated the ability of the hybrid functional to accurately describe the pressure-induced spin crossover behaviors of strongly correlated materials such as Fe-bearing MgO, MnPS 3 , and CsV 3 Sb 5 . It should be noted that for the study of Lu–N–H materials the hybrid functional method outperforms the GGA + U method.…”
Section: Introductionsupporting
confidence: 70%
“…The first-principles calculation was performed utilizing the Vienna ab initio Simulation Package (VASP). , All structures, including the lattice constants and the atomic positions, are fully relaxed based on the Heyd–Scuseria–Ernzerhof functional (HSE06) with a separation parameter of 0.2 and a default mixing parameter of AEXX = 0.25. This default setting in HSE06 is widely applied in studying various types of correlated materials and there is a lot of typical research inferring that this set of parameters in HSE06 successfully describes strongly correlated systems. The cutoff energy for plane wave expansion is set to 400 eV. The energy and force convergence thresholds are set to 1 × 10 –6 eV and 0.01 eV Å –1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the local magnetic moment was argued to be absent [37], the observation of the anomalous Hall effect in KV 3 Sb 5 [38] strongly favors the presence of a local magnetic field, hence the local spins. The first-principles electronic structure calculations also suggested there exist local magnetic moments in CsV 3 Sb 5 [23,24]. The result, the ratio 123 T 1 / 121 T 1 of Sb approaches to 3.4 at zero temperature limit [20], demonstrates that the process involving magnetic fluctuations dominates in spin-lattice relaxation at low temperature in CsV 3 Sb 5 .…”
Section: Introductionmentioning
confidence: 77%
“…Once such Kagome compounds [3] become superconductive [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], the long-term searching relationship between quantum spin liquid phase and unconventional superconductivity seems link with each other; recently found novel Kagome lattice compounds AV 3 Sb 5 (A = K, Rb, Cs) have been attracting great research interest . Through recent great efforts, many physical properties of AV 3 Sb 5 , including the electronic structures [3,[22][23][24][25], normal-state [3,27] and superconducting-state properties [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] have gradually become clear. Several theoretical models were also proposed to address the chirality of the charge-density-wave state [31,32] and superconductivi...…”
Section: Introductionmentioning
confidence: 99%